Peroneal Tendon Instability in Intra-Articular Calcaneus Fractures: A Retrospective Comparative Study and a New Surgical Technique. Issue 3 (March 2016) - Ketz, John P.; Maceroli, Michael; Shields, Edward; Sanders, Roy W.
Abstract : Objective: To compare the prevalence of peroneal tendon instability as determined by intraoperative evaluation versus preoperative computed tomography (CT) scans, and to identify specific risk factors that correlate with tendon instability. Design: Retrospective comparative study. Setting: Level 1 trauma hospital. Patients: Patients with operatively treated intra-articular calcaneus fractures managed between January 1, 2002 and December 31, 2012 were reviewed for evidence of peroneal tendon instability. Of 254 fractures, 155 intra-articular calcaneus fractures met inclusion criteria and were available for final analysis. Intervention: Operative notes were reviewed to confirm intraoperative testing for superior peroneal retinaculum (SPR) integrity and peroneal tendon stability. Preoperative CT scan and plain radiographs were evaluated for presence of peroneal tendon dislocation, fibular fracture or "fleck" sign, excessive lateral wall displacement, and/or calcaneal fracture-dislocation. Main Outcome Measures: Peroneal tendon stability was determined with intraoperative assessment of the intact SPR and its confluence with the peroneal tendon sheath. The incidence of peroneal tendon instability on intraoperative assessment was compared with preoperatively identified tendon dislocation on CT scan. Prevalence of peroneal tendon dislocation was determined using each diagnostic method. Risk factors for tendon instability were identified using a multivariate regression model. Results: There was significantly higher prevalence of peroneal tendon instability as determined by preoperative imaging (30%; n = 47/155) compared with intraoperative retinaculum testing (11.6%; n = 18/155) ( P < 0.001). Intraoperative tendon instability was significantly associated with increased fracture classification severity, fibular fracture/"fleck" sign, and fracture-dislocation. Conclusions: Intraoperative evaluation of the SPR should be used in conjunction with preoperative imaging for diagnosis of peroneal instability in the setting of operatively treated, intra-articular calcaneus fractures. Level of Evidence: Diagnostic Level IV. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.